Role of Calmodulin in Neurodegeneration and Neuroprotection - Kurochkina, Natalya; Rudrabhatla, Parvathi (Mini Reviews in Medicinal Chemistry, 2025)
Intracellular calcium (Ca2+) levels are critical in maintaining cellular activities and are tightly regulated. Neuronal degeneration and regeneration rely on calcium-binding proteins. Calmodulin (CaM) is a calcium sensor and the primary regulator of receptors and ion channels that maintain calcium homeostasis. The calmodulin binding domains are present in proteins that serve as risk factors and biomarkers associated with Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, Amyotrophic Lateral Sclerosis, and other neurodegenerative diseases, suggesting calmodulin ligands as emerging therapeutic targets for treatment. Inhibiting CaM to develop new therapies has drawbacks, as CaM is a ubiquitous molecule involved in many regulatory pathways. Recently, new strategies for disrupting CaM interactions with its targets have shown promising approaches to treatment.The structures of human CaM, its binding proteins, and inhibitors are well studied, with particular emphasis on the conservation of CaM amino acid sequences and the ability to bind protein fragments of high sequence variability, which exhibit common characteristics of amphipathic helices carrying basic amino acids.In this review, we discuss structural characteristics of CaM and its ligands in the context of transcriptional regulation. Specific binding of CaM to (1) basic region/helix-loop-helix/leucine zipper and (2) helix-turn-helix high mobility group box containing Sox families of transcription factors highlights common features of CaM binding sequences, which suggest their regulatory functions. We describe key proteins involved in neurodegeneration and transcription factors subject to calmodulin regulation that are candidates for the development of new approaches to treating neuronal diseases.
Keywords: neuroprotection